Towards a Phenomenology of Digital Sociality: Two Perspectives - Vaičiulis, Rokas (Religija ir kultūra, 2024)
The phenomenology of sociality responds to the dilemma of other minds by presuming the primordially intersubjective and embodied nature of intentional communicative acts. I propose, then, to consider the phenomenology of digital sociality as the field of research dedicated to investigate the specificity of the nature of intersubjectivity and embodiment constituted by digital communication media. By dividing the discussed variety of descriptive phenomenological accounts regarding digitally mediated embodied relationships (including Shanyang Zhao, Lucy Osler and Dan Zahavi, Rebecca A. Hardesty and Ben Sheredos and others) into the trajectories of extension (digitally mediated communication as the eidetic variation of generally embodied communicative acts) and pluralism (epistemology as well as ontology and socially normative practices intrinsic to the specific digital communication platform) I aim to demonstrate the topical tendencies and explanatory strategies that are developed in the attempts to deliver digital communication platform-sensitive phenomenological descriptions, often with the help of Alfred Schutz’s and Maurice Merleau-Ponty’s concepts.